Self-stigma in patients with schizophrenia: Impact and management - Ociskova, Marie; Prasko, Jan; Holubova, Michaela; Latalova, Klara; Sollar, Tomas; Zatkova, Marta; Slepecky, Milos; Bocek, Jonas (Neuro-endocrinology letters, 2023)
BACKGROUND: Prejudices against individuals with schizophrenia can interfere with diagnostic and treatment processes, particularly with the patient's further adaptation and reintegration. Self-stigma could have significant detrimental consequences for patients suffering from psychotic disorders, including schizophrenia. METHOD: This paper reviews findings about self-stigma connected to schizophrenia. The PubMed database used the keywords to find the papers published from January 1997 to March 2023, and 189 articles were included in the review process. RESULTS: The schizophrenia-related stigma decreases patients' self-confidence, worsens their social functioning, and impedes daily functioning. Feelings of embarrassment are prominent in many patients with schizophrenia. Self-stigma predicts many unfavourable outcomes - more severe social anxiety and depressive symptoms, lower self-confidence, hopelessness, worse social functioning, lower quality of life, worse treatment cooperation, and lower adherence to medication adherence. Addressing self-stigma in psychoeducation or psychotherapy may increase the patient's stigma resistance and well-being. Self-help groups present an underutilised but potentially effective strategy. CONCLUSION: Stigma presents a common issue in patients with schizophrenia. Targeting the issue in clinical management or psychotherapy may be beneficial. Still, more high-quality intervention studies are needed.
Keywords: psychotické poruchy; schizofrenie; sebepojetí; Humans; lidé; Quality of Life; Self Concept; Social Stigma; psychoterapie; kvalita života; společenské stigma; Schizophrenia; Psychotic Disorders; Psychotherapy